Wear Mechanism of Abrasive Gas Jet Erosion on a Rock and the Effect of Abrasive Hardness on It. (7th February 2019) - Liu, Yong; Zhang, Huidong; Ranjith, Pathegama Gamage; Wei, Jianping; Liu, Xiaotian
Abstract : The existing erosion models of abrasive gas jet tend to neglect the effects of the rebounding abrasive. To address this shortcoming, abrasive wear tests were conducted on limestone by using an abrasive gas jet containing different types of particles and with different standoff distances. The results indicate that erosion pits have the shape of an inverted cone and a hemispherical bottom. An annular platform above the hemispherical bottom connects the bottom with the side of the pit. The primary cause of the peculiar pit shape is the flow field geometry of the gas jet with its entrained particles. There is an annular region between the axis and boundary of the abrasive gas jet, and it contains no abrasive. Particles swirling around the axis form a hemispherical bottom. After rebounding, the abrasive with the highest velocity enlarges the diameters of both the hemispherical bottom and erosion pit and induces the formation of an annular platform. The surface features of different areas of the erosion pit are characterized using a scanning electron microscope (SEM). It can be concluded that the failure modes for different locations are different. The failure is caused by an impact stress wave of the incident abrasive at the bottom. Plastic deformation is the primary failure mode induced by rebounding particles at the sides of the hemispherical bottom. The plastic deformation induced by the incident abrasive and fatigue failure induced by the rebounding abrasive are the primary failure modes on the annular platform. Fatigue failure induced by rebounding particles is the primary mode at the sides of the erosion pits. The rock failure mechanism that occurs for particles with different hardness is the same, but the rock damaged by the hard abrasive has a rougher surface.